Acquired Epidermodysplasia Verruciformis in a Child with Atopic Dermatitis. Issue 3 (3rd September 2012) - Fernandez, Kristen H.; Rady, Peter; Tyring, Steven; Stone, Mary S.
<x xml:space="preserve">Abstract</x> Abstract: A 4‐year‐old girl with an established diagnosis of atopic dermatitis, previously severe and treated with cyclosporine, developed widespread papules that demonstrated changes consistent with epidermodysplasia verruciformis on biopsy. Human papilloma virus (HPV) typing was performed and was consistent with epidermodysplasia verruciformis‐type HPV (type 5). These lesions rapidly resolved with a 2‐week course of imiquimod. Rapid resolution and no family history of epidermodysplasia verruciformis make this most consistent with acquired epidermodysplasia verruciformis. This case is the first reported case of acquired epidermodysplasia verruciformis in a child without the human immunodeficiency virus and may be linked to cyclosporine use, which also has never been previously reported.